Eighty-eight International Accounting Problems in Rank Order of Importance: A DELPHI Evaluation. - Burns, Thomas J.; Loveland, Terry L. (The Accounting Review, 1981)
Reviews the book "Eighty-Eight International Accounting Problems in Rank Order of Importance: A Delphi Evaluation," by George M. Scott and Pontus Troberg.